Importance of health guidance for family members of children with sickle cell disease - Sarah Vieira Figueiredo; Letícia Alexandre Lima; Débora Pena Batista e Silva; Raquel de Maria Carvalho Oliveira; Macedônia Pinto dos Santos; Ilvana Lima Verde Gomes
ABSTRACT Objective: To know the main health guidance needs of family members of children with sickle cell disease. Method: Qualitative research, developed in a pediatric reference hospital of Ceará State, between April and May 2017, through the participation of 12 family members of children with sickle cell disease. The data were collected through semi-structured interviewees and analyzed according to the Bardin's Thematic Categorical Analysis. Results: The relatives had divergent opinions about what this pathology would be and expressed the expectation of being broadly guided, from general information (signs and symptoms) to more complex ones about the disease, including major complications and ways of preventing them. Final considerations: The health fragility due to the punctual and/or meager guidance provided to family members reflects the importance of increasing knowledge and clarifying doubts of these relatives about the disease, which makes it urgent to develop health education strategies by multiprofessional teams.